Model of Islamic History Learning in Majelis Taklim in Indonesia As-Syafi’iyah - Rizqi, Fatimah Tur; Syafuri, B.; Kultsum, Umi (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This research aims to describe the communication models and teaching methods used by the ustaz in delivering religious material in majelis taklim. This research uses a qualitative approach with a descriptive method, with data obtained from interviews, observations, and literature review, namely The method of da'wah such as hikmah emphasizes wisdom in delivering messages, adjusting the delivery method to the context and characteristics of the message recipients, while mujadalah involves constructive discussions and dialogues to clarify and strengthen arguments, often in the context of debates and disagreements. This was used long before mau'idhah hasanah became the main focus of this method, delivering teachings with a gentle and wise approach, and tailored to the characteristics of the audience. And mau’idhah hasanah has been used since the time of the Prophethood, initially to convey teachings to the community and the early spread of Islam. after Prophet Muhammad (PBUH) was appointed as a messenger, and it was used and developed during the Mecca and Medina periods.